Analysis of laboratory and serological test results in patients with acute brucellosis during follow‐up. Issue 3 (9th February 2022) - Ta, Na; Yu, Ruiping; Liang, Hanwei; Zhang, Wenqiang; Song, Litao; Fan, Menguang; Wen, Yongjun
Abstract: Background: The laboratory test results and serum‐specific antibodies of patients with acute brucellosis initial infection were followed up and analyzed. Methods: 70 patients in Hohhot City, Inner Mongolia Autonomous Region, with acute brucellosis were followed up for 360 days. Serum samples were collected at 0, 15, 30, 60, 90, 180, and 360 days after diagnosis and analyzed by Rose Bengal plate test (RBPT), colloidal gold test paper (GICA), and test tube agglutination test (SAT). The serum‐specific antibodies IgG and IgM were detected. Results: RBPT results: False negative (‐) gradually increased with the extension of the course of disease, with the largest change in 30–60 days after diagnosis, and the constituent ratio increased by 12.9%. GICA results: The false negative increased with the course of disease, and the constituent ratio of false negative was 20.0% after 180 days of diagnosis. SAT results: 1:100 positive showed a ladder like decrease with the increase in the course of disease, and the largest decrease was 90–180 days, with a decrease of 34.3% in the constituent ratio. 360 days after diagnosis, the constituent ratio of positive was only 14.3%. During the follow‐up period, the IgG average value fluctuated and the average IgM value decreased. Conclusion: The false‐negative results of RBPT, GICA, and SAT increased with the course of disease, and the false‐negative rates were higher than 20% after half a year. IgM level is beneficial to the early diagnosis of brucellosis, while IgG level is helpful to the judgment of brucellosis stage. Abstract : Brucellosis is a zoonotic disease caused by gram‐negative bacilli. In this study, patients with primary brucellosis infection were followed up, and their laboratory test results and serum specific antibody titers were tracked and analyzed within 360 days after the diagnosis of brucellosis.